Analisis Pengaruh Parameter Pemesinan Terhadap Kekasaran Permukaan Baja A36 Menggunakan Metode Respon Surface - anggun cahyani; Pranowo Sidi; Dhika Aditya (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
A large material removal rate and minimal surface rigidity are the desired objectives of this study with the right process parameters to obtain a large material response rate and a minimum surface hardness. The parameters used are spindle speed, feed rate and depth of cut. The experimental design is based on the response surface methodology of a box behnken design. The trials were randomized in three replications to produce a more optimal result. The results of the research showed that the influence of the parameter on the material removal rate is spindle speed with 0.442, feed rate with 0,000 and depth of cut with 0,000. parameter feed rate and deep of cut are stated to be significantly influenced. On the other hand, the influence of the parameter on the surface rigidity is that spindle speed with a of 0.017, feed rate with a of 0,000 and depth of cut has a of 0.074. Furthermore, the combination of the most optimal parameters for the material response variable removal rate and surface rigidity is the spindle speed of 2006 RPM, the feed rate of 252 mm/min and the depth of cut of 0.1965 mm.